PEOPLE PERCEPTION TOWARDS PUBLIC READING ROOM SERVICE OF CITY GARDEN IN SURABAYA - Rahmat, Dimas; Widya, Galih; Dwi, Sandi; Rahmawati, Mardiyah; Audria, Alvinna; Chidya. P, Whopy; H, M. Al Azhar.; Maya. S, Karina Elita; Alfiyah, Ninik; Avriany. D, Yindi; Megawati, Nikmahtin; Karolyn. P, Dhani; Fithriyah, Aida; Yudha, Herlina (Record and Library Journal, 2015)
Surabaya as Literacy City has been starting in National Education Day 2 May 2014 and also rising their features and facility like Public reading room, Library and Mobile Library. And we also Concern with some worst Realty about literacy System in Surabaya, such as had been Close some library in Shoping Center in Surabaya, like in Cito Mall, Royal Plaza and Kapas Krampung Plaza cause some problem in operasional System have causing other problem can disturb many achievement of Surabaya as Literacy City. We have should to continue it for another Public Reading Room in Surabaya canât be like another Closed public reading room. And we must to minimalize it with Resources learningÂ  through the efforts of reviewing public reading room of the service as an essential element in an information centre. In order to show better utilization of the future for the public after the assessment is the primary focus of our study was to determine the extent to which the services at the general public reading room so that the future can be used as a positive response for public reading room. The method used is quantitative approach with the method of data collection in the form of an explanatory through observation, literature, and the distribution of questionnaires to the respondents in all four public reading room in park city of Surabaya. Overall from 4 to place our study showed that the frequency of public perception in total into the bad category based on indicators of Vincent theory who leads a balanced way of internal and external factors. It shows that the public reading room services that already exist is still considered very less than the maximum and the indication of the need for an increase in the promotion, facilities and innovation program for the future.